Difusão dos bancos de leite humano no Brasil um estudo à luz da perspectiva institucional - Godri, Luciana (2012)
The objective of this dissertation is on understanding how actions associated with institutional entrepreneurship and the isomorphic pressure mechanisms conditioned the diffusion of human milk banks in Brazil from 1985 to 2012. The work is justified theoretically on explaining the diffusion process integrating the interested social action on creating institutions and the isomorphic contextual pressures. The practical justification lies on dealing with strategies to induct cooperation in order to institutionalize something. The research was developed using institutional theory, analyzing first the agency of interested social actors in the role of institutional entrepreneurs and then the isomorphic contextual pressure. The analysis to explain the spread of human milk banks in Brazil was made by integrating the two analytical categories and treating the influence of one to another. This case of study is a qualitative, in a descriptive exploratory level and in a longitudinal temporal perspective. It used thematic content analysis with the aid of software NVivo to analyze the data collected through interviews and documentary analysis. The data showed that Instituto Fernandes Figueira qualifies as a social interested actor in the diffusion of human milk banks in Brazil and that it used its social skills to create frames and mobilize resources in order to induce the cooperation of other actors in the organizational field. The data also showed the isomorphic contextual pressures being shaped and shaping the field, in a recursive process. It was observed, then, that what was ideational and was in the discourse of social actors, had become the institutional structure that now governs the field. In this movement, the agents action starts losing the interest on institutional change going thought to the interest on institutional maintenance.